PENINGKATAN KADAR Zn DALAM BERAS ASE LAPANG DAN VARIETAS LAINNYA - Edy Edy; Bakhtiar Ibrahim (Percetakan Umi Toaha Makassar, 2017)
Rice is a staple food for most of Indonesia's population. Therefore it is necessary to increase the production and quality with Nitrogen and Zing fertilization. The long-term goal of this study is to improve and obtain new methods of fertilization to increase production and protein content and Zn rice. Specific targets to be achieved are to reduce malnutrition of Indonesia's poor. The method used for this purpose to be achieved is by deciphering the appropriate mixture of N and Zn so that the protein and Zn content in the rice increases. Research conducted 2 years. year I was performed in a plastic house in a pot experiment and obtained results showing Zn application at a concentration of 400 mg ZnO / l water + nitrogen fertilization of 160 kg / ha increased the dry weight of a grain of 11.8%. weight of 1000 seeds 4.8%. protein 4.8% and Zn 26.4%. Based on the result of the research of Year I. conducted the research of Year II by applying the formula on 4 varieties. directly in the fields. Research II is designed in a separate Plot Design. The main plot is the formulation (F) consisting of 200 mg ZnO / l water +160 kg N / ha (F1) and 400 mg ZnO / l water + 160 kg N / ha (F2). The subplot is a variety (V) consisting of Field Ase (V1). Pulu Mandoti (V2). Ciherang (V3). Santana (V4). repeated 3 times. This year's research obtained results showing concentrations of 400 mg ZnO / L water + 160 kg N / ha increased dry weight of grain, and tended to increase protein and Zn levels in rice. Rice Varieties Ase Field and Pulu Mandoti higher levels of protein and Zn then followed by Varieties Ciherang and Cisantana.